Utensil manipulation during initial treatment of pediatric feeding problems. Issue 4 (24th October 2014) - Wilkins, Jonathan W.; Piazza, Cathleen C.; Groff, Rebecca A.; Volkert, Valerie M.; Kozisek, Jennifer M.; Milnes, Suzanne M.
<x xml:space="preserve">Abstract</x> Children with feeding disorders exhibit a variety of problem behaviors during meals. One method of treating problem mealtime behavior is to implement interventions sequentially after the problem behavior emerges (e.g., Sevin, Gulotta, Sierp, Rosica, & Miller, 2002). Alternatively, interventions could target problem behavior in anticipation of its emergence. In the current study, we implemented nonremoval and re‐presentation of bites either on a spoon or on a Nuk for 12 children with feeding problems. The nonremoval and re‐presentation treatment improved feeding behavior for 8 of 12 children. Of those 8 children, 5 had lower levels of expulsions, and 4 of the 8 children had higher levels of mouth clean with the Nuk than with the spoon. We describe the subsequent clinical course of treatment and present follow‐up data for 7 of the 8 children who responded to the nonremoval and re‐presentation treatment with the spoon or Nuk. The data are discussed in terms of potential reasons why the utensil manipulation improved feeding behavior for some children.